Association between PT, PT-INR, and in-hospital mortality in critically ill patients with tumors: A retrospective cohort study - Liang, Jia-Dong; Qin, Zuo-An; Yang, Jin-Hao; Zhao, Chao-Fen; He, Qian-Yong; Shang, Kai; Li, Yu-Xin; Xu, Xin-Yu; Wang, Yan (Frontiers in Public Health, 2023)
Objectives Prothrombin time (PT) and PT-INR are independent predictors of mortality in patients with cancer. The PT and PT-INR of cancer patients are independent predictive variables of mortality. However, whether the PT or PT-INR is related to in-hospital mortality in severely ill patients with tumors remains unknown. Participants The data relevant to seriously ill patients with tumors were obtained from 208 hospitals spread throughout the USA. This research included a total of 200,859 participants. After the samples were screened for patients with combination malignancies and prolonged PT-INR or PT, the remaining 1745 and 1764 participants, respectively, were included in the final data analysis. Primary and secondary outcome measures The key evaluation methodology was the PT count and PT-INR, and the main outcome was the in-hospital mortality rate. Results After controlling for confounding variables, we found a curvilinear connection between PT-INR and in-hospital mortality (p<0.001), and the inflection point was 2.5. When PT-INR was less than 2.5, an increase in PT-INR was positively associated with in-hospital mortality (OR 1.62, 95% CI 1.24 to 2.13), whereas when PT-INR was greater than 2.5, in-hospital mortality was relatively stable and higher than the baseline before the inflection point. Similarly, our study indicated that the PT exhibited a curvilinear connection with in-hospital mortality. On the left side of the inflection point (PT <22), a rise in the PT was positively linked with in-hospital mortality (OR 1.08, 95% CI 1.04 to 1.13, p<0.001). On the right side of the inflection point, the baseline PT was above 22, and the in-hospital mortality was stable and higher than the PT count in the prior range (OR 1.01, 95% CI 0.97 to 1.04, 0.7056). Conclusion Our findings revealed that there is a curved rather than a linear link between the PT or PT-INR and in-hospital mortality in critically ill cancer patients. When these two laboratory results are below the inflection point, comprehensive therapy should be employed to reduce the count; when these two laboratory results are above the inflection point, every effort should be made to reduce the numerical value to a value below the inflection point.